2017
DOI: 10.1590/2317-1782/20162016119
|View full text |Cite
|
Sign up to set email alerts
|

Remote follow-up to speech-language intervention for children with Autism Spectrum Disorders (ASD): parents’ feedback regarding structured activities

Abstract: Purpose: This paper aims to present the first descriptions of experiences of parents and caretakers of children with Autism Spectrum Disorders (ASD) enrolled as mediators in a structured program of speech-language intervention with remote follow-up. Methods: Research with focus on speech-language intervention for children with ASD was carried out with remote follow-up. Forty parents were instructed to perform daily activities focused on communication and interaction with their children, at home, for a period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 7 publications
(7 reference statements)
0
12
0
5
Order By: Relevance
“…By guidance and the development of intervention programs that include families, the speech therapist can provide parents with conditions to assume more active roles in establishing appropriate communication environments for children with ASD, which provide successful interactive experiences 7 .…”
Section: Introductionmentioning
confidence: 99%
“…By guidance and the development of intervention programs that include families, the speech therapist can provide parents with conditions to assume more active roles in establishing appropriate communication environments for children with ASD, which provide successful interactive experiences 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Por meio da orientação e do desenvolvimento de programas de intervenção que incluem as famílias, o fonoaudiólogo pode fornecer aos pais condições de assumirem papéis mais ativos no estabelecimento de ambientes de comunicação apropriados para crianças com TEA e que proporcionam experiências interativas bem-sucedidas 7 .…”
Section: Introductionunclassified
“…Barbosa and Fernandes (10) reported an intervention proposal with remote monitoring -by undergraduate students, with systematic supervision -of activities parents of children with ASD should conduct at home with their children. The results indicate progress in all measures assessed before and after the remote monitoring period (10) .…”
mentioning
confidence: 99%
“…Barbosa and Fernandes (10) reported an intervention proposal with remote monitoring -by undergraduate students, with systematic supervision -of activities parents of children with ASD should conduct at home with their children. The results indicate progress in all measures assessed before and after the remote monitoring period (10) . In a subsequent study, the same authors identified that only 40% of the parents of children with ASD were able to conduct all the proposed activities and reported difficulties with the household routine and children's behavior (11) .…”
mentioning
confidence: 99%